MAKNA KATA UN ‘BAWA’ DALAM BAHASA BIAK, PAPUA KAJIAN METABAHASA SEMANTIK ALAMI - Hugo Warami (Balai Bahasa Provinsi Papua, 2019)
This article aims to describe and reveal a grain of Biak language lexicon based on semantic features different from the features of the other features. In semantics, a lexicon form fields can be described completely meaning to get the features behind it. This study will describe the meaning of Un ‘take’ in the language of Biak - Papua packaging metalanguage natural semantics of theory (MSA). MSA theory is designed to mengeksplikasikan all meaning, either lexical meaning, grammatical meaning, and illocutionary. Natural conditions of a language can be able to maintain a form of meaning and one meaning for one form. Results of this study indicate that the basic meaning of Un ‘take’ in Biak has eleven sub-type of meaning.